Application of the Simple Additive Weighting (SAW) Method in a Decision Support System for Prioritizing Public Complaint Handling at the Bandung Cipta Bintar Agency - Feri Alpiyasin; Rendi Sutendi (Journal of Multimedia Technology and Applied Software, 2025)
The increasing number of services at the Office of Public Works, Building Construction, and Spatial Planning (Cipta Bintar) of Bandung City has encouraged the agency to develop a web-based platform to simplify and accelerate service processes. One of the features provided on this platform is the public complaint service. However, the existing complaint feature still has several shortcomings, including the absence of a report status tracking function, the lack of complaint category classification to ensure reports are directed to the appropriate department, and the absence of a priority determination mechanism for complaint handling. So far, complaints have only been processed based on the order of submission, without considering the level of urgency or potential impact. This research proposes a solution by developing a web-based public complaint system that integrates the Simple Additive Weighting (SAW) method as the core of the prioritization process. SAW is chosen because it enables objective and systematic calculations based on five main criteria: Level of Urgency, Potential Impact, Type of Complaint, Complexity of the Problem, and Report Duration. Through the implementation of SAW, the system is not only able to provide report status information and category classification but also deliver measurable recommendations for handling priorities. The results of this study indicate that the application of the SAW method is the key to improving the effectiveness, efficiency, and responsiveness of public complaint services at Cipta Bintar Bandung City, as it successfully addresses the limitations of the previous system that relied solely on submission order